Graphitization of Coconut Shell Charcoal for Sulfonated Mesoporous Carbon Catalyst Preparation and Its Catalytic Behavior in Esterification Reaction - Fahmi Fahmi; Widiyastuti Widiyastuti; Heru Setyawan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Here, we reported the utilization of coconut shell charcoal used for solid acid catalysts and its performance in the esterification reaction of acetic acid and methanol. The graphitization of coconut shell charcoal was carried out by the calcination and KOH activation at the temperature of 400 °C for an hour and continued at the temperature of 800 °C for an hour under nitrogen flow resulted in graphitic carbon. The effect of the addition of KOH activation was observed by varied the weight ratio of coconut shell charcoal as raw material (RM) and KOH. The selected weight ratio of RM:KOH was 1:1, 1:2, and 1:4. The resulted graphitic carbon was sulfonated by heating with the sulfuric acid to obtain a solid acid catalyst. The sulfonic time was evaluated for 5 and 10 hours. The generated particles were characterized to examine the morphology, the crystallinity, the specific surface area, the chemical bonding, and the ionic capacity using Scanning Electron Microscopy (SEM), X-Ray diffraction (XRD), nitrogen gas absorption-desorption, Fourier Transform Infrared Spectroscopy (FTIR), and titration method, respectively. The best condition for graphitization of raw material is the use of RM:KOH = 1:4, resulting in the highest surface area reaching 1259.67 m2/g and the most dominant of the sulfonic group of −SO3 bond. Furthermore, increasing the sulfonating time from 5 to 10 hours led to the increase of the yield of esterification reaction from 85% to 96.57% for graphite synthesized using RM:KOH = 1:4. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).